Pemberdayaan Guru Madrasah Tsanawiyah Melalui Pelatihan Inovatif untuk Meningkatkan Keterampilan Guru dalam Merancang Pembelajaran Mendalam - Hasanah, Rusi Ulfa; Simbolon, Novi Tari; Siregar, Elida Tuti; Adawiyah, Robiatul; Sibarani, Sariayu; Simangunsong, Herlina; Siregar, Cristyani; Saputri, Lilis (Jurnal Pengembangan dan Pengabdian Masyarakat Multikultural, 2025)
This community service program aimed to empower Madrasah Tsanawiyah (MTs) teachers in enhancing their skills to design deep learning through innovative training. The program was conducted at MTs Al-Fauzi and involved 20 teachers as participants. Initial analysis revealed that most teachers were in the medium (45%) and low (35%) categories, while only 20% achieved the high category. This indicated that teachers faced challenges in integrating higher-order thinking skills (HOTS), problem-solving, and project-based learning into their lesson plans. After the training, a significant shift occurred: the low category decreased to 10%, the medium category dropped to 30%, and the high category increased to 60%. These results demonstrate that innovative training through hands-on practice, collaborative discussion, and lesson design simulation was effective in improving teachers’ skills. However, the program had several limitations, including limited training duration, short-term evaluation, and a relatively small number of participants. Therefore, continuous mentoring and follow-up activities are recommended to ensure that the improved skills are consistently applied in daily classroom practices.